2009
DOI: 10.3342/ceo.2009.2.4.175
|View full text |Cite
|
Sign up to set email alerts
|

Th2 Responses Elicited by Nasal Epithelial Cells Exposed to House Dust Mite Extract

Abstract: ObjectivesRespiratory epithelial cells are the first site of interaction of allergens with the immune system. The aim of this study was to examine the effect of epithelial cells, which were stimulated with house dust mite (HDM) extracts, on the immune response of peripheral blood mononuclear cells (PBMCs).MethodsPrimary nasal polyp epithelial cells were exposed to dermatophagoides pteronyssinus and dermatophagoides farina for 48 hr, and then the supernatant and cells were collected. After stimulation with HDM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Der p1 contains cysteine protease activity, which causes cytokine release, facilitates allergen translocation across epithelial cell layers (63), and increases neutrophil ROS levels (48). A recent study reported that HDM induced proinflammatory cytokines IL-6 and IL-8 in a dose- and time-dependent manner (64). Our study demonstrated a similar cytokine profile, namely induction of IL-2, IL-4, and IL-17 in MLE-12 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Der p1 contains cysteine protease activity, which causes cytokine release, facilitates allergen translocation across epithelial cell layers (63), and increases neutrophil ROS levels (48). A recent study reported that HDM induced proinflammatory cytokines IL-6 and IL-8 in a dose- and time-dependent manner (64). Our study demonstrated a similar cytokine profile, namely induction of IL-2, IL-4, and IL-17 in MLE-12 cells.…”
Section: Discussionmentioning
confidence: 99%
“…HDM extracts were shown not only to induce increases in the permeability of bronchial mucosa but also to trigger the release of pro-inflammatory cytokines such as IL-6, IL-8, monocyte chemotactic protein (MCP)-1, GM-CSF and IL-1β in activated airway epithelial cells [23,24,25,26,27]. Both events were largely dependent on protease activity of HDM extracts.…”
Section: Effects Of Hdm Extracts On Airway Innate Immune Cellsmentioning
confidence: 99%
“…The resulting hydration of the inhalated HDMs triggers the rapid and total discharge of major allergenic proteins and Der P1 is a major allergen of HDM. Nasal epithelial cells produced larger amounts of IL-8 and GM-CSF with HDM extracts [14]. The nasal cavity is the most common site for Staphylococcus aureus colonization and their enterotoxins act as superantigens due to their ability to bind MHC class II molecules and directly activate the nasal epithelial cells [15].…”
Section: Discussionmentioning
confidence: 99%